OP0123 SYMPTOMS IN FIRST DEGREE RELATIVES OF PATIENTS WITH RHEUMATOID ARTHRITIS: EVALUATION OF DATA FROM THE SYMPTOMS IN PERSONS AT RISK OF RHEUMATOID ARTHRITISQUESTIONNAIRE. (June 2019) - Costello, Ruth; Haris, Mohammad; Humphreys, Jenny; Sergeant, Jamie; Stirling, Fiona; Raza, Karim; Schaardenburg, Dirkjan van; Bruce, Ian N.
Abstract : Background: First degree relatives (FDRs) of people with rheumatoid arthritis (RA) have a four-fold increased risk of developing RA. The Symptoms in Persons At Risk of Rheumatoid Arthritis (SPARRA) questionnaire was developed to document symptoms in persons at risk of RA. Objectives: To describe i) symptoms in a cohort of FDRs of patients with RA using the SPARRA questionnaire and (ii) the proportion of these symptoms in participants with detectable autoantibodies or elevated CRP. Methods: The PRe-clinical EValuation of Novel Targets in RA (PREVeNT-RA) study is a cohort of FDRs of patients with RA, who are without inflammatory arthritis and aged ≥30 years at recruitment. Consented participants completed a study questionnaire and provided a blood sample for measurement of Rheumatoid factor (RF), anti-cyclic citrullinated peptide antibodies (anti-CCP) and C-reactive protein (CRP). Those who agreed to future contact were asked to complete the SPARRA questionnaire. This questionnaire asks about a variety of joint symptoms, other symptoms and severity of joint pain in specific parts of the body, allowing identification of symmetrical, small and large joint pain. We identified subjects with moderate/severe symptoms and rheumatoid distribution (symmetrical, small and large joints). We also stratified these groups by 1) seropositivity (RF or anti-CCP positive) and 2) elevated CRP. Results: By July 2018, 1866 participants had completed the study questionnaire and provided a blood sample. Of those 870 (47%) returned the SPARRA questionnaire and in this subgroup, 43 (5%) were seropositive and 122 (14%) had elevated CRP. The most frequently reported symptoms were sleep problems (20%), joint pain (18%) and fatigue (17%). The proportion with joint stiffness, symmetrical joint pain or small joint pain was higher in the seropositive and elevated CRP groups. This difference was statistically significant in those with elevated CRP, respective difference in proportions (95% CI) of small and symmetrical joint involvement were 10.7 (1.9 to 19.5) and 11.5 (3.2 to 19.8) (Table 1). Conclusion: This is the first time the SPARRA questionnaire has been applied in FDRs of patients with RA. Some of the most prevalent symptoms e.g. sleep problems or fatigue, did not identify patterns suggestive of progression to RA. However, the distribution of joint involvement (symmetrical, small joint pain), was in keeping with RA features. This part of the questionnaire may be useful in identifying individuals most likely to develop RA. Disclosure of Interests: Ruth Costello: None declared, Mohammad Haris: None declared, Jenny Humphreys: None declared, Jamie Sergeant: None declared, Fiona Stirling: None declared, Karim Raza: None declared, Dirkjan van Schaardenburg: None declared, Ian N. Bruce Grant/research support from: Genzyme Sanofi, GlaxoSmithKline, Consultant for: AstraZeneca, Eli Lilly, GlaxoSmithKline, ILTOO Pharma, MedImmune, Merck Serono, Speakers bureau: GlaxoSmithKline, UCB Pharma